Multi-Agent Simulation in the Inter-Organizational Trust Model and Knowledge Sharing in the Automotive Industry - Rizana, Afrin Fauzya; Ramadhan, Fadillah (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
Two organizations can share knowledge to determine the success of their collaboration. Effectiveness in sharing knowledge affect the organizational performance and trust between organizations. This study aims to identify the implementation of multi-agent simulations to increase confidence in sharing knowledge between organizations. A multi-agent simulation approach was used in this study. The research model was adopted from previous research. Several hypotheses and path coefficients had tested in simulation models. The results of this study showed that multi-agent simulation is suitable to be implemented as a problem-solving method for a complex problem such as knowledge sharing. Besides, this study found the role of individual factors such as likability and expertise on the success of sharing knowledge between organizations.